Stunting Prevention Stunting Prevention in the Low Birth Weight Status: A Qualitative Study in Bengkulu City - Suryani, Desri; Krisnasary, Arie; Pratiwi, Bintang Agustina; Yandrizal, Yandrizal (International Journal of Medical Science and Clinical Research Studies, 2024)
In 2022, 47 child cases with low birth weight were found in Indonesia. It is one of the risk factors for stunting. The role of mothers is very necessary in preventing children from being stunted. This study aims to analyze what efforts are made by the mothers so that the children with a history of low birth weight do not experience stunting. This type of research is qualitative research. The research was conducted in Bengkulu City, in May - July. Seven mothers with a birth history of Low Birth Weight (LBW) became the research informants. Interview guidelines were used to gather information. Furthermore, the data were analyzed with stages of analysis (reduction, presentation, and conclusion). Mothers realized that stunting is a condition in which children experience impaired growth and development. However, all mothers said the cause is malnutrition and intestinal worms. Therefore, the precautions taken by mothers are only related to intake. The mothers implement early initiation of breastfeeding, exclusive breastfeeding, and continue to give until the age of two years, complete immunization, and concern for the child’s diet. Especially for mothers who have children with a history of low birth weight, special assistance should be carried out and given comprehensive education about stunting prevention efforts, not only from dietary factors but also from environmental health